Pelatihan Budidaya Green House Melon Intanon di Kecamatan Banjar Margo, Tulang Bawang - Suci Amalia; Astri Shabrina; Ayu Dian Pratiwi Permatahati; Tika Leoni Putri (Wisanggeni: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT The cultivation training for Inthanon melon variety using greenhouse and Internet of Things (IoT) technology was conducted at Nurul Fattah Islamic Boarding School in Tulang Bawang as part of a community service program applying the Participatory Action Research (PAR) approach. This activity aimed to enhance the capacity of students and staff in cultivating melons using modern and sustainable practices. The PAR method was implemented through four stages: planning, action, observation, and reflection. The training included the delivery of cultivation materials, seedling and plant maintenance practices, the use of automated irrigation systems, measurement of fruit sweetness using a Brix meter, and harvesting with a self-pick agro-tourism approach. Results showed a significant improvement in participants' understanding; out of 15 participants, only 33% answered the pre-test correctly, while the post-test success rate increased to 87%. Innovations such as IoT utilization and direct marketing strategies proved effective in supporting the sustainability of the boarding school’s agribusiness. This activity had a positive impact on pesantren economic development and serves as a replicable model of adaptive and educational community-based agribusiness. Keywords: Melon Cultivation, Greenhouse, Participatory Action Research, IoT, Islamic Boarding School.